A Review of Teacher Feedback Strategies on Student’s Writing Performance in EFL Contexts - Geral Dien Stefanny Sapulete; Lailatul Musyarofa; Yudy Prasetyo (Universitas Pahlawan Tuanku Tambusai, 2026)
This paper presents a comprehensive synthesis of recent empirical research on teacher feedback strategies and their contributions to improving English as a Foreign Language (EFL) students’ writing performance. Writing is a cognitively demanding skill that requires learners to coordinate vocabulary, grammar, organization, and genre conventions. Although previous studies have demonstrated that teacher feedback can improve writing performance, the existing literature remains fragmented regarding which feedback strategies are most effective, under what conditions they produce positive outcomes, and how learner characteristics influence their effectiveness. Previous research has often examined individual feedback techniques or specific instructional contexts, making it difficult to establish broader patterns across different EFL settings. This gap highlights the need for a systematic synthesis of recent empirical evidence. This study employs a descriptive qualitative approach with a systematic literature review design to examine peer-reviewed, open-access articles published between 2021 and 2026 from ScienceDirect, Springer Open, Frontiers, and MDPI. Twelve studies were analyzed using thematic analysis to identify patterns in feedback types, implementation, and learning outcomes. The findings indicate that direct corrective, indirect facilitative, and metalinguistic feedback serve different pedagogical functions. Overall, feedback is most effective when it is timely, specific, adaptive, and encourages active learner engagement and self-regulated revision. The review contributes a broader synthesis of recent evidence and highlights the importance of differentiated feedback practices in EFL writing instruction.